Exploring Alienation and Knowledge: A Comparative Study of H.P. Lovecraft and Giacomo Leopardi - Cipriani, Enrico (Dialogoi. Rivista di studi comparatistici, 2024)
This essay examines the themes of alienation and knowledge in the works of H.P. Lovecraft and Giacomo Leopardi. While both authors grapple with the insignificance of humanity in the face of an indifferent universe, their responses diverge significantly. Lovecraft’s cosmicism presents knowledge as a source of existential dread and isolation, culminating in a profound psychological crisis for his characters. Conversely, Leopardi’s cosmic pessimism acknowledges the cruelty of existence while advocating for human solidarity and ethical engagement as responses to despair. By presenting the authors’ philosophies, this study highlights how Lovecraft and Leopardi articulate the complexities of human existence and the pursuit of knowledge in a vast and indifferent cosmos.